Perancangan dan Pengujianalat Pemetik Pepaya Tipe Semi Mekanis - Mustaqimah Mustaqimah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2012)
To harvest papaya by using a long pole may break it. It can influence the price reduction or even it cannot be sold if it drops to the ground. Harvesting by using hand is also possible but this methode could cause injury due to harvester fingers. So, it was required to design a tool for harvesting papaya in order to keep the high quality, increase the quantity and introduce a convenient method in harvesting papaya for farmers. A semi mechanical papaya harvester was designed at Agricultural Machinery and Equipment Laboratory, Syiah Kuala University and then it was evaluated at papaya farming in Alue Rindang Village, Seulimum Sub district, Aceh Besar District from January until March 2010. The tool has dimension by 335 cm in length, 23 cm in width and 5.5 kg in weight. The tool could harvest 222 papaya fruits per hour whereas by using traditional method the farmers could harvest only 133 papaya fruits per hour. Therefore, the use of papaya harvester is promising to improve the quantity and quality of papaya fruits. Keywords: papaya, harvester